(untitled) (Medical Forum Monthly, 2020)
Objective: To examine the functional outcomes of flexible intramedullary nailing in children presented with open tibial fractures. Study Design: Retrospective study Place and Duration of Study: This study was conducted at the Orthopaedic Department, Federal Government Polyclinic Hospital Islamabad from January 2019 to December 2019. Materials and Methods: Thirty two patients of either gender with ages 5 to 14 years presented with open tibial fractures were enrolled in this study. Patient’s detailed demographics were recorded. All patients treated with flexible intramedullary nailing. Radiological assessment was done. Complications associated to procedure were examined. Functional outcomes were analyzed according to the Flyn’s criteria. Follow-up was taken at 6 months postoperatively. Results: There were 24 (75%) male and 8 (25%) were females. 14 (43.75%) patients were ages 5 to 10 years and 18 (56.25%) patients were ages 11 to 14 years. RTA was the commonest etiology found in 15 (46.88%) patients followed by fall from height in 10 (31.25%) patients. None of patient had nonunion. Mean union time was 3.86±1.27 months. Complications found in 3 (9.38%) patients in which 1 patient with wound infection, 1 had shortening of leg and 1 with delayed union. 22 (68.75%) patients had excellent, 7 (21.88%) had good, 3 (9.38%) had fair and none of patient had poor functional outcomes. Conclusion: Flexible intramedullary nailing for open tibial fractures in children is safe and effective treatment modality. Union of bone achieved all the patients and majority of patients had excellent functional outcomes.